Phytochemical Composition and Antioxidant Activity of Flavonoid-Rich Extracts of Elsholtzia ciliata Collected in Dak Lak Province, Vietnam - To, Dao-Cuong; Ngu, Truong Nhan; Nguyen, Van-Tinh; Hanh, Dam Thi Bich; Phong, Truong Ba; Nguyen, Phi-Hung; Tran, Manh Hung (Current Overview on Pharmaceutical Science Vol. 6, 2023)
Elsholtzia ciliata (Thunb.) Hyland (Lamiaceae) is widely distributed in the Central Highlands (Tay Nguyen) and Southern Vietnam. In traditional medicine, E. ciliata has been used for the treatment of colds, fever, flu, headache, dizziness, rheumatism, pharyngitis, abdominal pain, diarrhea, vomiting, measles, and itchy sores. This study aimed to determine the total flavonoid content by high-pressure liquid extraction method and evaluate the antioxidant activity of flavonoid-rich extracts of E. ciliata collected in the three regions in Dak Lak province. The methanol extracts were obtained by high-pressure liquid extraction method from the leaves of E. ciliata collected in Buon Ma Thuot city (KG-BMT), Cu M'gar district (KG-CM), and Buon Don district (KG-BD). The total flavonoid content (TFC) from the methanol extracts obtained in three regions was 82.30696 mg quercetin equivalent (QE)/g extract for the Cu M'gar district, 62.26035 mg QE/g extract for the Buon Don district, and 27.08587 mg QE/g extract for Buon Ma Thuot city. The methanol extracts showed high levels of antioxidant capacity in the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay with IC50 ranging from 0.70 to 1.98 mg/mL. Flavonoid compounds were identified as apigenin, apigenin-O-b-glucoside, ethyl gallate, catechin, epicatechin, and quercitrin from the methanol extracts in three regions by ultra-high performance liquid chromatography (UHPLC).